“In situ” corneal and contact lens thickness changes with high resolution OCT - González-Méijome, José Manuel (2012)
Purpose: To show the utility of high resolution spectral domain optical coherence tomography (HR SOCT) for the in situ evaluation of epithelial, stromal and contact lens (CL) thickness changes under closed-eye conditions without lens removal. Settings: Clinical and Experimental Optometry Research Lab, University of Minho, Portugal. Methods: Eight young healthy patients wore a thick soft CL during 90 minutes under closed-eye conditions and measures of epithelial and stromal corneal thickness were obtained at regular intervals using a HR SOCT (Copernicus HR, Optopol Tech. SA, Poland). Results: Minimal changes in epithelial thickness were detected with a transient statistically significant increase in epithelial thickness in the fellow control eye 30 minutes after insertion (p=0.028). A significant and progressive increase in stromal thickness up to 8% after 90 minutes of lens wear was observed at a constant rate of 2.5% 50 every 30 minutes, being statistically significant in all observations (p<0.001). Fellow control eye also showed a significant increase in stromal thickness at a much lower rate of 0.5% every 30 minutes. Lens thickness decreased significantly by 2% after 90 minutes of lens wear under closed eye conditions (p<0.001). Individual analysis showed that all eyes displayed stromal swelling, while only half of them showed epithelial swelling. Conclusion: Increase in stromal thickness and a slight decrease in lens thickness were observed in response to a hypoxic stimulus under closed eye conditions. High resolution spectral domain HR SOCT is a powerful tool to investigate in vivo the physiological interactions between cornea and contact lenses.